Incongruencias entre el triunfo militar patriota y las concesiones establecidas en el Acta de Capitulación de Ayacucho - Aibar Ozejo, Mario Eduardo (2024)
In the Battle of Ayacucho the royalist army was defeated, however, an onerous capitulation was signed for the Peruvian nation. The victorious army was subject to conditions largely favorable to the defeated royalist army, whose military leaders did not have the capacity to impose and have real command over significant military nuclei or detachments. In accordance with the foregoing, it is proposed that the act of Capitulation of the Battle of Ayacucho (December 1824) was the product of the agreement between the officers of the republican army and the liberal officers of the royalist army (with a proclivity towards constitutional monarchy), within the framework of the political changes in Spain (end of the liberal triennium and return of the absolute monarchy) with the correlation of persecution of liberals in Spain and America. The Act of Capitulation took place through a process of negotiation “between peers”, when the royalist army no longer had any parity but rather was militarily subordinated to the patriotic army. This negotiation did not focus on the principles and future development of the nascent republic but on the immediate interests prioritized by the military of both armies.